THE EFFECT OF USING CHINESE WHISPER GAME ON STUDENTS’ FIVE BASIC TENSES MASTERY (A Study at the Eleventh Grade Students of SMA Negeri 1 Angkola Selatan in 2018/2019 Academic Year) - Aulia Ulfah Hasibuan (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The aims of this research are to know: 1) The extent of the application of Chinese Whisper Game in teaching five basic tenses at the eleventh grade students of SMA Negeri 1 Angkola Selatan, 2) The extent of the students’ five basic tenses mastery before and after taught by using Chinese Whisper Game at the eleventh grade students of SMA Negeri 1 Angkola Selatan, 3) Whether any significant effect of Chinese Whisper Game on students’ five basic tenses mastery at the eleventh grade students of SMA Negeri 1 Angkola Selatan. The population of this research is all of the eleventh grade students of SMA Negeri 1 Angkola Selatan which consist of 97 students. Sample were 35 students which taken by using purposive sampling. The research method that used was experimental method. To collect the data the writer used observation sheet and test as an instrument. The mean score of the application of Chinese Whisper Game was 3.1, it was categorized “Very good”. The result of data analysis shows that ttest=9.24 while ttable=2.03. it means that ttest is higher than ttable. So, the hypothesis is accepted. It means that there is significant effect of Chinese Whisper Game on students’ five basic tenses mastery at the eleventh grade students SMA Negeri 1 Angkola Selatan. Keywords: Chinese Whisper Game, Five Basic Tenses Mastery Abstrak: Tujuan penelitian ini adalah untuk mengetahui 1) pengaplikasian dari Chinese Whisper Game 2) untuk mengetahui sejauh mana penguasaan lima tenses dasar siswa 3) untuk mengetahui apakah ada efek yang signifikan dari Chinese Whisper Game terhadap penguasaan lima tenses dasar siswa di kelas sebelas SMA Negeri 1 Angkola Selatan. Populasi dalam penelitian ini adalah semua siswa kelas sebelas yang terdiri dari 97 orang. Sampelnya adalah 35 siswa yang diambil melalui sampling purposive. Metode penelitian yang digunakan adalah metode eksperimental. Untuk mengumpulkan data peneliti menggunakan lembar observasi dan tes sebagai instrumennya. Nilai rata-rata dari pengaplikasian Chinese Whisper Game adalah 3.1, dikategorikan “Sangat bagus”. Hasil dari analisis data menunjukkan bahwa ttest=9.24 while ttable=2.03. Itu berarti ttest lebih besar dari ttable. Hipotesis diterima. Itu berarti ada efek yang signifikan dari Chinese Whisper Game terhadap penguasaan lima tenses dasar siswa kelas 11 SMA Negeri 1 Angkola Selatan. Keywords: Penguasaan Lima Tenses Dasar, Chinese Whisper Game